Optical properties and location of phenolic compounds in plant cuticles - González Moreno, Ana (UMA Editorial, 2023)
The main findings from the present Doctoral Thesis are summarized hereunder. The location and identification of the main cuticle components throughout tomato fruit development was achieved combining hyperspectral data from Confocal Raman Microscopy and multivariate analysis. The spontaneous isomerization between the flavonoids naringenin chalcone and naringenin as well as the potential aggregation among them in an environment mimicking the plant cuticle were explored via quantum calculations. Moreover, optical properties of tomato fruit cuticles during development have been analysed in detail. Accordingly, the individual and combined photochemistry of the main phenolic compounds accumulated in ripe tomato fruit cuticles, naringenin chalcone and p-coumaric acid, were also examined. Additionally, a non-radiative mechanism by which cuticle phenolics, specifically p-coumaric acid ubiquitously present in plants, attenuate incident UV-B radiation was proposed.
Keywords: Cutícula vegetal - Tesis doctorales; Phenolic compounds; Plant cuticle; Photoprotection; Optical properties